EFFECT OF EMPLOYEES’ RELATIONSHIP MANAGEMENT AND MANAGERIAL EFFECTIVENESS IN AGATU LOCAL GOVERNMENT EDUCATIONAL AUTHORITY - UCHERWUHE SAMUEL IGBABEE (International Studies Journal)
The main objective of the study is to examine the effect of employee relationship management on managerial effectiveness. The specific objectives of the study are to determine effect of communication, shared values/goals, and employee trust on managerial effectiveness in Agatu Local Government Education Authority, Benue State, Nigeria.  The study adopted survey research design, the sample size of 293 selected from a population of 1100 employees. The study found a significant positive effect of employees’ relationship management on managerial effectiveness. The studyconcludedthat organizations should invest more in a strong employees’ relationships management as it significantly affects managerial effectiveness, specifically, communication, shared goals/values and trust have a significant positive effect on managerial effectiveness.The study recommended that communication should be highly invested into as every organization need effective communication for managerial effectiveness, Local Government Education Authorities should always enshrine a culture-oriented principles that can intimate employees with organizational goals/shared values for flexible operations that enhances managerial effectiveness and management of Local Government Education Authorities should provide an environment of trust that allows employees to actively participate in the decision-making process. This is because a working environment with a highly trusting atmosphere is the foundation for harmonious employees’ relationship.